1995
DOI: 10.1111/j.1467-9280.1995.tb00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Right-Hemisphere Memory Superiority: Studies of a Split-Brain Patient

Abstract: Six experiments explored hemispheric memory differences in a patient who had undergone complete corpus callosum resection The right hemisphere was better able than the left to reject new events similar to originally presented materials of several types, including abstract visual forms, faces, and categorized lists of words Although the left hemisphere is capable of mental manipulation, imagination, semantic priming, and complex language production, these functions are apparently linked to memory confusions—con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
52
1
8

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 34 publications
14
52
1
8
Order By: Relevance
“…In the domain of verbal memory, such a proposal predicts that the LH is more likely to remember gist (and to mistakenly remember inferred, schemaconsistent information), whereas the RH is more likely to remember the specific stimuli that were encountered (i.e., the form). Metcalfe et al (1995) studied recognition memory in a split-brain patient and found results supporting this view. After studying a list of categorically related words, the patient was more successful at rejecting new words from the same category when these were projected to the LVF/ RH.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…In the domain of verbal memory, such a proposal predicts that the LH is more likely to remember gist (and to mistakenly remember inferred, schemaconsistent information), whereas the RH is more likely to remember the specific stimuli that were encountered (i.e., the form). Metcalfe et al (1995) studied recognition memory in a split-brain patient and found results supporting this view. After studying a list of categorically related words, the patient was more successful at rejecting new words from the same category when these were projected to the LVF/ RH.…”
supporting
confidence: 56%
“…This raises the question of whether there might be unique ways in which the two hemispheres encode, maintain, and retrieve information about any given stimulus type. One proposal is that the RH stores information fairly veridically, whereas the LH is more likely to "interpret" stimuli and make inferences from them (Metcalfe, Funnell, & Gazzaniga, 1995). In the domain of verbal memory, such a proposal predicts that the LH is more likely to remember gist (and to mistakenly remember inferred, schemaconsistent information), whereas the RH is more likely to remember the specific stimuli that were encountered (i.e., the form).…”
mentioning
confidence: 99%
“…An attempted hypothesis at this level of cognitive functioning might be informed by theories of self monitoring and reality monitoring. The argument would likely find support from findings made in studies assessing the role of the right frontal lobe in the retrieval and monitoring of self related memories, as well as those evaluating the function of the right hemisphere in verifying the truthfulness of recollections (Craik et al, 1999;Fletcher, Shallice, Frith, Frackowiak, & Dolan, 1998;Metcalfe, Funnell, & Gazzaniga, 1995;Schacter, Curran, Galluccio, Milberg, & Bates, 1996;Shanks & Venneri, 2002;Venneri, Shanks, Staff, & Della Sala, 2000). It is worth considering in the first place, therefore, whether cognitive disturbances suggesting a wider dysfunction of frontal lobe functions are observed either transiently or chronically in association with neurologically defined lack of awareness.…”
Section: Discussionmentioning
confidence: 95%
“…During the past several years, there has been growing interest in the brain structures and processes that are related to memory errors and distortions, as explored in experiments with various patient populations (cf. Kroll, Knight, Metcalfe, Wolf, & Tulving, 1996;Metcalfe, Funnell, & Gazzaniga, 1995;Moscovitch, 1995;Parkin, Binschaedler, Harsent, & Metzler, 1996;Reinitz, Verfaellie, & Milberg, 1996;Schacter, Curran, Galluccio, Milberg, & Bates, 1996) and in neuroimaging studies (Duzel, To gain insight into the brain mechanisms underlying this memory illusion, we have recently examined false recognition in amnesic patients (Schacter, Verfaellie, & Pradere, 1996;Schacter, Verfaellie, & Anes,1997). Amnesic patients exhibit severe difªculties remembering recent experiences as a consequence of damage to the medial regions of the temporal lobes and related structures in the diencephalon, yet retain normal perceptual and linguistic functions along with IQ scores within the normal range (Parkin & Leng, 1993;Squire, 1994).…”
Section: Introductionmentioning
confidence: 99%